Design and Characterization of Punica granutum Seed Oil-loaded Cream: Assessment of In vitro Antimicrobial Potential (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present investigation was started with aim to formulate and assess the antimicrobial potential of Punica granatum seed oil cream. The P. granatum seed oil cream was formulated using glyceryl monostearate and other lipids like stearic acid as well as cetyl alcohol. The formulated cream was then evaluated with respect to physicochemical properties and in vitro antimicrobial activity against Escherichia coli. The formulated oil loaded cream showed acceptable physicochemical properties like pH, spreadability, type of emulsion and viscosity which confer its suitability for topical application. In addition to this, the in vitro antimicrobial potential of oil loaded cream against E. coli was also found to be acceptable. Thus, formulated cream could be promising alternative for topical application of P. granatum seed oil with better antimicrobial potential.